Pengukuran Nilai Densitas pada Minyak Pelumas Sepeda Motor dengan Gelombang Ultrasonik - Ahmad Fauzi Firmansyah; Agus Indra Gunawan; Indra Adji Sulistijono; Denny Hanurawan (Jurnal Rekayasa Elektrika, 2022)
Density is a measure of the mass of each unit volume of an object, the higher the density of an object, the greater the mass of each volume. The density value can be used to distinguish the characteristics of lubricating oils that are prone to contamination with solid or liquid particles. The density value is also affected by changes in temperature, the higher the temperature of the lubricating oil, the smaller the density value. The regulations in force in Indonesia with the ASTM D1298-12b standard density test method state that the measurement uses a temperature of 15℃. In this study, the density measurement value was obtained at a temperature of 28℃ so it required a value conversion using the ASTM 53B table about the density correction factor. The technique of testing the material without damaging the test object using an ultrasonic sensor is used to measure the density value of motorcycle lubricating oil. Measurements are made by transmitting a 3 MHz ultrasonic trigger signal that can penetrate each medium with different characteristics. The received echo signal produces information about the distance between the medium, the speed of sound, and the acoustic impedance. The results of the measurement of 11 samples of motorcycle lubricating oil both in new and used conditions using the acoustic impedance method resulted in an accuracy of 93,6% or 0,058 kg/dm3 when compared to the value measured using a pycnometer. The MPX-2-C sample measurement showed the lowest error of 0,41% or 0,004 kg/dm3.